ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PROGRAM KEAHLIAN TEKNIK KOMPUTER JARINGAN DI SMK RAJASA SURABAYA - Prasetyo, Ilham Andhy; Harimurti, Rina; Baskoro, Farid; Rakhmawati, Lusia (Universitas Negeri Surabaya, 2021)
Problem Based Learning (PBL) learning model is a learning model based on the problems experiencedby students during the process of gaining knowledge. This learning model can train students to learnindividually in finding solutions based on existing problems. Thus PBL is a learning model that can beapplied to students in vocational schools. The purpose of this study is to describe the application of thePBL learning model. Judging from the formulation of the problem in this study, which is about how thedescription of the application of the PBL learning model in class X students of the Network ComputerEngineering Expertise Program at SMK Rajasa Surabaya. This research uses descriptive research witha qualitative approach. Data were collected using interview techniques and filling out questionnaires.The data obtained were then analyzed using several stages, namely collecting data, reducing data,presenting data, and drawing conclusions. The results of the study show that the application of theProblem Based Learning (PBL) learning model makes class X students in the TKJ department thinkmore critically to solve problems that have been faced, according to the responses from students in code3. Based on the results of interviews in code 5, the PBL model is also able to stimulate students to be more active so that students can express their opinions with confidence. Some of the difficultiesexperienced by students while using the PBL model are the difficulty of finding information to solve theproblems given by the teacher, the basic abilities possessed by students make it difficult to solveproblems. With online learning during the pandemic, the PBL model does not work optimally, so therelationship between students and teachers and relationships between students do not work well.